Strategies for Optimising Uptake of Assisted Partner Notification Services Among Newly Diagnosed HIV Positive Adults at Ndirande Health Centre, Malawi - Paul Chiwa Puleni; Alinane Linda Nyondo-Mipando (Taylor & Francis Group, 2022)
ABSTRACTUNAIDS Fast-Track goals for 2025 include ensuring that 95% of the people with HIV know their HIV status. In 2019, the Malawi Ministry of Health introduced its approach for achieving this: an active index testing (AIT) policy with assisted partner notification services (APNS). Under this policy, health centers can actively reach out to a contact of newly-diagnosed HIV positive client (the index) to offer voluntary HIV testing services. However, APNS uptake has been sub-optimal at many health facilities. This qualitative study considers strategies to optimize the uptake of APNS among newly-diagnosed HIV positive clients at Ndirande Health Center in Blantyre, Malawi. We conducted in-depth interviews, between February and April 2020, with 24 participants, including new HIV positive index clients, their sexual partners, and key health workers. We employ a maximum variation purposive sampling technique. Thematic inductive and deductive data analysis was done manually according to the social-ecological model. Interviewees discussed various strategies for optimizing APNS uptake among newly diagnosed HIV-infected clients. Interpersonal strategies included maximizing the use of client profiling techniques and sensitization on APNS to create demand. Institutional-level strategies were also suggested, such as providing transportation for home visits, strengthening referral notification approaches, and additional training for health workers. Policy-level recommendations included introducing home-based partner testing and intensifying use of partner notification slips. APNS is a key strategy to maximize HIV case identification. However, achieving optimal APNS in Malawi requires strengthening existing strategies and conducting additional research to identify other APNS strategies tailored to the local context.